Analisis Scientometric tentang Kematangan Transformasi Digital dalam Penelitian dan Pengembangan - Riski Riski; Achmad Nurmandi; Muhammad Younus; Herman Lawelai; Wahdania Suardi (Society, 2025)
This study uses a scientometric approach to analyze the evolution and maturity of digital transformation in research and development (R&D) over the past decade. For this purpose, bibliometric data from the Scopus database was searched from 2015 to 2024. The resulting dataset of 495 articles was then exported in CSV format. The results showed that the evolution of digital transformation has had a major impact on research progress over the previous decade, with digital transformation maturity (DTM) emerging as an important concept in understanding how organizations and sectors adapt to technological advances. This study used scientometric analysis to explore the development and trends of DTM research over the past decade. The study then focuses more deeply on evaluating digital maturity, integrating technology in decision-making processes, and exploring specific sectors that have received relatively less attention in the existing literature from an industry perspective. The findings suggest that companies need to adopt a more systematic digital transformation strategy, optimize the use of data in management, and apply innovative technologies to improve efficiency and competitiveness.